2016
DOI: 10.1111/risa.12692
|View full text |Cite
|
Sign up to set email alerts
|

Does Medical Risk Perception and Risk Taking Change with Age?

Abstract: Across adulthood, people face increasingly more risky medical problems and decisions. However, little is known about changes in medical risk taking across adulthood. Therefore, the current cross-sectional study investigated age-related differences in medical risk taking with N = 317 adults aged 20-77 years using newly developed scenarios to assess medical risk taking, and additional measures designed to evaluate risk-taking behavior in the medical domain. Greater expected benefits on the Domain-Specific Risk-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…Rather, numeracy levels (whether objective or subjective) were largely unrelated to participants’ responses. This finding is in line with an earlier study (Hanoch, Rolison, & Freund, ) that also found no link between numeracy and medical risk taking. Thus, our finding suggests that improving numeracy skills might not help solve the problem of misjudging risks and benefits of medical procedures.…”
Section: Discussionsupporting
confidence: 92%
“…Rather, numeracy levels (whether objective or subjective) were largely unrelated to participants’ responses. This finding is in line with an earlier study (Hanoch, Rolison, & Freund, ) that also found no link between numeracy and medical risk taking. Thus, our finding suggests that improving numeracy skills might not help solve the problem of misjudging risks and benefits of medical procedures.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have examined the age-related differences in risk perception using hypothetical reallife situations (e.g., Hanoch et al, 2018;Sun and Sun, 2019). Recently, the COVID-19 outbreak gave researchers the opportunity to focus on the perception of risk across the lifespan applied to a real-life situation (Bruine de Bruin, 2020;Pasion et al, 2020;Guastafierro et al, 2021;Kivi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggest that, holding all other factors constant, our sampled older commuters would be more risk‐taking than young ones, while higher‐income subjects would be less risk‐taking. Existing evidence on systematic heterogeneity in risk‐taking is mixed (see, for example, Hao et al ., 2016; Hanoch et al ., 2018). Mata et al .…”
Section: Modelling Results: Observed Heterogeneity In Risk Takingmentioning
confidence: 99%